Cardiac Surgery in Patients With Trisomy 13 and 18: An Analysis of The Society of Thoracic Surgeons Congenital Heart Surgery Database. Issue 13 (2nd July 2019) - Cooper, David S.; Riggs, Kyle W.; Zafar, Farhan; Jacobs, Jeffrey P.; Hill, Kevin D.; Pasquali, Sara K.; Swanson, Sara K.; Gelehrter, Sarah K.; Wallace, Amelia; Jacobs, Marshall L.; Morales, David L. S.; Bryant, Roosevelt
Abstract : Background: Congenital heart disease is common in patients with Trisomy 13 (T13) and Trisomy 18 (T18), but offering cardiac surgery to these patients has been controversial. We describe the landscape of surgical management across the United States, perioperative risk factors, and surgical outcomes in patients with T13 and T18. Methods and Results: Patients in the Society of Thoracic Surgeons Congenital Heart Surgery Database with T13 and T18 who underwent cardiac surgery (2010–2017) were included. There were 343 operations (T13: n=73 and T18: n=270) performed on 304 patients. Among 125 hospitals, 87 (70%) performed at least 1 operation and 26 centers (30%) performed ≥5 T13/T18 operations. Operations spanned the full spectrum of complexity with 29% (98/343) being in the highest categories of estimated risk. The operative mortality rate was 15%, with a 56% complication rate. Preoperative mechanical ventilation was associated with an odds ratio of mortality >8 for both patients with T13 and T18 (both P <0.012) while presence of a gastrostomy tube (odds ratio, 0.3; P =0.03) or prior cardiac surgery (odds ratio, 0.2; P =0.02) was associated with better survival in patients with T18 but not patients with T13. Conclusions: Data from this nationally representative sample indicate that most centers offer surgical intervention for both patients with T13 and T18, even in highly complex patients. However, the overall mortality rate was high in this select patient cohort. The association of preoperative mechanical ventilation with mortality suggests that this subset of patients with T13 and T18 should perhaps not be considered surgical candidates. This information is valuable to clinicians and families for counseling and deciding what interventions to offer.